2021
DOI: 10.1002/jper.20-0623
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐146a and ‐155, upregulated by periodontitis and type 2 diabetes in oral fluids, are predicted to regulate SARS‐CoV‐2 oral receptor genes

Abstract: Background: Type 2 diabetes and periodontitis predispose to a higher risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Recent studies show upregulation of innate immuno-regulatory microRNA-146a and -155 in oral fluids of patients with type 2 diabetes as well as of patients with periodontitis. The aim was to investigate whether upregulation of these microRNAs may relate to patient susceptibility to the infection via modulation of SARS-CoV-2 cellular entry factors expression. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 42 publications
(66 reference statements)
1
48
0
Order By: Relevance
“…Among the 22 studies related to this topic, 15 were nonexperimental studies 12,[15][16][17][18][19]21,[23][24][25]27,28,30,32,35 ; there were seven experimental reports. 13,14,26,31,33,34,36 For 16, the type of article was clearly indicated; seven were original articles, 13,14,26,31,33,34,36 four were letters to the editor, 17,18,25,30 four were revi ews, 24,28,32,35 and one was a "commentary." 27 Among the six for which this was not clearly indicated, we considered that five were short reports 12,15,16,19,21 -one of which reported an ongoing clinical trial, 16 and one was a review.…”
Section: Hypotheses On the Relationship Between Periodontal Diseases And Covid-19 Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 22 studies related to this topic, 15 were nonexperimental studies 12,[15][16][17][18][19]21,[23][24][25]27,28,30,32,35 ; there were seven experimental reports. 13,14,26,31,33,34,36 For 16, the type of article was clearly indicated; seven were original articles, 13,14,26,31,33,34,36 four were letters to the editor, 17,18,25,30 four were revi ews, 24,28,32,35 and one was a "commentary." 27 Among the six for which this was not clearly indicated, we considered that five were short reports 12,15,16,19,21 -one of which reported an ongoing clinical trial, 16 and one was a review.…”
Section: Hypotheses On the Relationship Between Periodontal Diseases And Covid-19 Study Characteristicsmentioning
confidence: 99%
“…27 Among the six for which this was not clearly indicated, we considered that five were short reports 12,15,16,19,21 -one of which reported an ongoing clinical trial, 16 and one was a review. 23 The information relating to the topic found in the papers was the SARS-CoV-2 entry mechanism, [12][13][14]16,18,21,[24][25][26][27][28][30][31][32]36 the mechanism of how periodontitis might influence the entry of SARS-CoV-2 into cells or might worsen COVID-19, [15][16][17][18][19]21,[23][24][25][26][27][28]30,[32][33][34][35][36] and antiviral targets to treat COVID-19 (►Table 1). 14,18,24,27…”
Section: Hypotheses On the Relationship Between Periodontal Diseases And Covid-19 Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Roganović reports that it is possible that the presence of diabetes and periodontitis in patients infected by SARS-CoV-2 causes an increase of two microRNAs (-146a and -155) which in turn causes a greater expression of the ACE2 receptor. This seems to favor the mechanisms of SARS-CoV-2 infections in periodontal tissues; however, this study was carried out through a bioinformatics analysis, so clinical or in vitro studies are needed to confirm these findings [ 49 ]. Marouf et al determined that the presence of periodontitis in SARS-CoV-2 positive patients is associated with a greater severity of the disease and an increased risk of death [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has indicated that, in general, endogenous human miRNAs (small, single-stranded~22 nt RNAs, such as miRNA-146a) might have a significant antiviral role and hence may be useful to the host in an innate-immune defense by targeting the single-stranded viral ribonucleic acid (ssvRNA) genomes of several different neurotropic viruses, such as SARS-CoV-2, and function to downregulate or modulate their expression [77,78]. To this end, and to quote just one recent example, RNA sequencing and other analytical genetics in RNA-based sequence studies have shown that at least~160 of the~2650 of the 18-22 nt naturally occurring human single-stranded miRNAs have per-fect complementarity within the miRNA-mRNA 'seed region' of the SARS-CoV-2 ssvRNA genome, and these include the unique hsa-miRNA-146a ribonucleotide sequence and those of other related microRNA gene families [47,73,[79][80][81]. Interestingly, the apparent lack of nucleic acids detectable within the prion particle indicates that some yet poorly understood pathological mechanism is responsible for the prion-mediated upregulation of miRNA-146a when neurons are confronted with infection by these neurological-disease inducing sialoglycoproteins [16,53,60,75,82,83].…”
Section: Neurotropic Viral-mediated Induction Of Hsa-mirna-146a-5pmentioning
confidence: 99%